2006
DOI: 10.1152/ajpheart.01104.2005
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of contractility by myocyte-derived arginase in normal and hypertrophied feline myocardium

Abstract: . Modulation of contractility by myocytederived arginase in normal and hypertrophied feline myocardium. Am J Physiol Heart Circ Physiol 290: H1756 -H1762, 2006. First published December 3, 2005 doi:10.1152/ajpheart.01104.2005.-L-Arginine, the sole substrate for the nitric oxide (NO) synthase (NOS) enzyme in producing NO, is also a substrate for arginase. We examined normal feline hearts and hearts with compensated left ventricular (LV) hypertrophy (LVH) produced by ascending aorta banding. Using Western blot … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 43 publications
1
21
0
2
Order By: Relevance
“…[2][3][4][5][6] In our study, normotensive WKY rats exhibit substantial arginase activity in all organs studied, which is associated with the expression of both arginase isoforms in the brain, lungs and heart, and with the expression of arginase I in the liver and arginase II in the kidney. These data are in accordance with previous studies reporting the expression of arginase I and/or II in neurons, 16,17 cardiomyocytes, 18,19 pulmonary epithelial, endothelial, smooth muscle cells, fibroblasts and alveolar macrophages, 20 in renal proximal straight tubules and inner medullary collecting ducts, 21,22 as well as in hepatocytes. 21 A new finding of our study is the age-dependent increase in arginase activity in the heart of WKY rats.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…[2][3][4][5][6] In our study, normotensive WKY rats exhibit substantial arginase activity in all organs studied, which is associated with the expression of both arginase isoforms in the brain, lungs and heart, and with the expression of arginase I in the liver and arginase II in the kidney. These data are in accordance with previous studies reporting the expression of arginase I and/or II in neurons, 16,17 cardiomyocytes, 18,19 pulmonary epithelial, endothelial, smooth muscle cells, fibroblasts and alveolar macrophages, 20 in renal proximal straight tubules and inner medullary collecting ducts, 21,22 as well as in hepatocytes. 21 A new finding of our study is the age-dependent increase in arginase activity in the heart of WKY rats.…”
Section: Discussionsupporting
confidence: 93%
“…These data suggest that cardiac arginase is a target of age-associated metabolic dysfunctions and complete recent studies showing increased vascular 23 and penile 24 arginase in old animals. Given that aging is associated with impaired myocardial contractility 25 and that arginase activity was reported to modulate cardiomyocyte contractility through an NO-dependent mechanism, 18,19 this result opens new avenues on the role of arginase in cardiac dysfunction associated with aging.…”
Section: Discussionmentioning
confidence: 99%
“…However, rather lower intracellular levels of L-arginine were reported in cardiomyocytes (42). Moreover, the expression of arginase II in mitochondria of mouse cardiac myocytes (122) and arginase I in feline cardiac myocytes (69) has been demonstrated. The activity of mtNOS may be impaired under the conditions whereby L-arginine concentration within the heart mitochondria is diminished.…”
Section: Heart Nossmentioning
confidence: 96%
“…[5][6][7][8] Increased arginase activity, therefore, leads to diminished production of NO. 6,[9][10][11][12] In vascular tissue, this further affects 2 important functions of NO: (1) cGMPdependent signaling and (2) modulation of protein function through S-nitrosylation. Several studies have demonstrated reciprocal regulation of arginase and NOS, where inhibition of arginase leads to increased NO activity.…”
mentioning
confidence: 99%